Analysis of impact of consumption of proton pump inhibitor on osseointegration of dental implants to the alveolar bone -a systematic critical appraisal - Lal, Abhishek; Umer, Fahad; Parkash, Om (Journal of the Pakistan Medical Association, 2023)
Proton pump inhibitors are one of the most frequently prescribed medicines primarily for reducing the production of gastric acid. Every medicine has some adverse effects associated with it, including effects on the bone tissues. Dental implant is one of the most preferred options for teeth replacement. The current literature review was planned to evaluate the association between intake of proton pump inhibitors and its impact on the bone around the dental implant. Literature review entailed search on Google Scholar, Web of Science and PubMed databases using a range of search terms. Chronic intake of proton pump inhibitors has been associated with decrease in the density of bone, which eventually leads to increased risk of dental implant failure. However, since limited studies have been carried out, further research is required, especially clinical trials, to evaluate the relationship between the intake of proton pump inhibitors and the failure of dental implants.